Method for preparing lithium manganese iron phosphate composite positive electrode material based on sol-gel method
The preparation of lithium manganese iron phosphate composite positive electrode material through ultrasonic/microwave auxiliary sol gel method and microwave gradient high-temperature sintering method is solved, and the problems of uneven material preparation and unstable electrochemical performance in the prior art are achieved, thus achieving high efficiency and ability of the material Control and environmentally friendly preparation significantly improves the performance of the material.
Patent Information
- Application Number
- CN202411326336.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-23
AI Technical Summary
In the preparation of lithium manganese iron phosphate composite cathode material, there are problems such as uneven mixing of raw materials, high reaction temperature, poor product batch consistency, easy to mix impurities and difficult to control the microstructure of the material, resulting in unstable electrochemical performance of the material. .
Ultrasonic/microwave assisted sol gel method and combined with microwave gradient high-temperature sintering method to prepare lithium manganese iron phosphate composite positive electrode material. The method includes preheating various salt solutions, mixing evenly, performing ultrasonic-microwave collaborative treatment in an ultrasonic microwave combination reaction system to form a fluffy honeycomb-like dry gel, followed by thermal decomposition and microwave sintering to obtain lithium manganese iron phosphate composite Positive electrode material.
The material preparation cycle is significantly shortened, the accuracy of temperature control is improved, the uniformity of the material is improved, and the resulting materials show excellent dispersion, electronic conductivity and stability.
Smart Images

Figure CN119390044A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a method for preparing lithium manganese iron phosphate composite positive electrode materials based on a sol-gel method. Background Art
[0002] As a core component of new energy industries such as electric vehicles (EV), hybrid electric vehicles (HEV) and large energy storage devices, lithium-ion batteries (LIB) have to improve their power density, energy density and cycle life. Among the raw materials of lithium-ion batteries, cathode materials are still the key to improving electrochemical performance and reducing total costs. x Fe 1-x PO4 is studied as the most promising cathode material for lithium-ion batteries due to its high energy density, good cycle stability and environmental friendliness.
[0003] At present, the main technical solution for preparing lithium manganese iron phosphate materials is the solid phase method. Although the solid phase method has a mature process and simple procedures, it has uneven raw material mixing, high reaction temperature, poor product batch consistency, easy mixing of impurities and difficulty in controlling the microstructure of the material. These shortcomings will directly affect the material's charge and discharge capacity performance, rate cycle performance and high and low temperature performance. Although the traditional sol-gel method has improved the mixing problem of raw materials to a certain extent, it still has problems such as the long gelation process and difficulty in precise control, easy agglomeration during the drying process, and difficulty in precise control of the crystal structure during high-temperature sintering, which leads to the instability of the material's electrochemical performance. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a method for preparing lithium manganese iron phosphate composite positive electrode material based on the sol-gel method, aiming to solve at least one technical problem in the background technology.
[0005] The present invention is achieved in that:
[0006] The present invention provides a method for preparing a lithium manganese iron phosphate composite positive electrode material based on a sol-gel method, the method comprising the following steps:
[0007] Preheating the lithium salt solution, the manganese salt solution, the ferrous salt solution, the phosphorus compound solution, and the complexing agent solution to preset temperatures respectively;
[0008] Under continuous stirring and heat preservation, the manganese salt solution and the complexing agent solution are first mixed uniformly, and then the ferrous salt solution, the phosphorus compound solution and the lithium salt solution are added in sequence, and concentrated ammonia water is added dropwise to obtain a reaction solution with a pH of 2 to 5;
[0009] The reaction solution is placed in an ultrasonic-microwave combined reaction system, and is subjected to ultrasonic treatment alone, ultrasonic-microwave synergistic treatment, and microwave treatment alone in sequence to obtain a fluffy honeycomb dry gel;
[0010] The dry gel is subjected to thermal decomposition treatment, and the obtained product is mixed with a carbon source in a preset ratio, and then ground and demagnetized in sequence to obtain a precursor powder;
[0011] In the microwave reaction system, the precursor powder was subjected to microwave gradient sintering at 200W to 450W under protective atmosphere conditions, and the powder product LiMn was obtained after cooling. x Fe 1-x PO4 / C is a lithium manganese iron phosphate composite positive electrode material.
[0012] Furthermore, the reaction solution is placed in an ultrasonic-microwave combined reaction system, and ultrasonic treatment alone, ultrasonic-microwave synergistic treatment, and microwave treatment alone are successively performed to obtain a fluffy honeycomb dry gel, and the specific operation is as follows:
[0013] The reaction container containing the reaction solution is placed in the ultrasonic microwave combined reaction system, and only the ultrasonic dispersion device is turned on to perform ultrasonic treatment on the reaction solution, with the ultrasonic power being 200W to 400W and the treatment time being 10min to 30min;
[0014] Then, the microwave heating device is turned on for ultrasonic-microwave coordinated treatment, the microwave power is set to 250W-500W, and the reaction time is 30min-60min;
[0015] When the reaction solution turns into a yellow sol, the ultrasonic dispersion device is turned off and the microwave heating treatment is continued until a fluffy honeycomb dry gel is formed.
[0016] Furthermore, the ultrasonic-microwave combined reaction system is also provided with a container containing deionized water.
[0017] Furthermore, the dry gel is thermally decomposed, the obtained product is mixed with a carbon source in a preset ratio, and then ground and demagnetized in sequence to obtain a precursor powder. The specific operation is as follows:
[0018] The dry gel is placed in a muffle furnace and heated to 300°C to 400°C for thermal decomposition for 3h to 6h;
[0019] After cooling to room temperature in the furnace, the pyrolysis product is taken out, and the pyrolysis product is mixed with the carbon source in a mass ratio of 8 to 12:1 and ground to obtain a uniform mixed powder;
[0020] The mixed powder is placed in a rotating demagnetizer and subjected to a demagnetization treatment in a magnetic field of 4000GS to 6000GS for 8 minutes to 12 minutes to obtain a precursor powder.
[0021] Furthermore, the carbon source is selected from glucose or sucrose.
[0022] Furthermore, in the microwave reaction system, the precursor powder is subjected to microwave gradient sintering at 200W to 450W under protective atmosphere conditions, and the specific operation is as follows:
[0023] First, sinter at 300°C to 450°C for 15 min at a microwave power of 200W to 250W;
[0024] Sintering at 800°C to 1000°C for 20min to 30min at a microwave power of 350W to 450W;
[0025] After cooling in the furnace, the final powder product LiMn x Fe 1-x PO4 / C;
[0026] Among them, the pressure during the sintering process is controlled to be 0.01MPa~0.5MPa.
[0027] Further, the lithium salt is selected from lithium hydroxide monohydrate, lithium nitrate, lithium acetate, lithium chloride or lithium oxalate;
[0028] The manganese salt is selected from manganese acetate, manganese carbonate, manganese sulfate, manganese nitrate or manganese chloride;
[0029] The ferrous salt is selected from ferrous nitrate, ferrous sulfate or ferrous chloride;
[0030] The phosphorus-containing compound is selected from phosphoric acid or phosphates, and the phosphates are selected from diammonium phosphate or triammonium phosphate;
[0031] According to the molar ratio, lithium salt: phosphorus-containing compound: manganese salt: ferrous salt = 1: (1.1-1.3): x: (1-x), 0.6≦x≦0.8.
[0032] Furthermore, the complexing agent is selected from citric acid; the molar ratio of the lithium salt to the complexing agent is 1:1-2.
[0033] Furthermore, the preset temperature of preheating is 70°C to 90°C.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention prepares lithium iron manganese phosphate composite positive electrode material through ultrasonic / microwave assisted sol-gel combined with microwave gradient high-temperature sintering, which significantly shortens the preparation cycle of lithium iron manganese phosphate material, improves the accuracy of temperature control, and effectively improves the uniformity of the material. The lithium iron manganese phosphate composite positive electrode material prepared by the present invention exhibits excellent dispersibility, electronic conductivity and stability.
[0036] 2. The process threshold of the present invention is low, the energy consumption is low, and the preparation process is green, environmentally friendly and pollution-free, which provides a new method of efficient, controllable and environmentally friendly for the preparation of high-performance lithium manganese iron phosphate materials.
[0037] 3. The present invention uses microwave assistance in the gelation and sintering process. Microwave heating can directly act on the molecules of the material, so that the reaction system can reach a uniform temperature distribution in a short time, thereby effectively and accurately controlling the temperature in the gelation process and sintering, shortening the gelation and sintering time, and improving production efficiency; in addition, a lower microwave power is used to gradually heat the material in the initial stage of microwave sintering to avoid the destruction of the material structure caused by a sharp temperature change; the microwave power is then increased in a gradient, which can more effectively promote the reaction degree of the material, and the overall sintering reaction time is short and the structure and performance of the material are maintained. At the same time, the gelation process is assisted by ultrasonic dispersion technology, which breaks the agglomerates in the gel through its cavitation effect and mechanical vibration, so that the particles are evenly dispersed; this helps to reduce the interaction force between particles during the drying process, prevent the occurrence of agglomeration, and thus prepare a more uniform particle size distribution, a more dense and orderly microstructure, and greatly improves the electronic conductivity and stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific implementation cases described herein are only used to explain the present invention and are not used to limit the present invention.
[0040] See also Figure 1 A method for preparing a lithium manganese iron phosphate composite positive electrode material based on a sol-gel method, the method comprising the following steps S11 to S15:
[0041] S11, preheating the lithium salt solution, the manganese salt solution, the ferrous salt solution, the phosphorus compound solution, and the complexing agent solution to preset temperatures respectively;
[0042] Weigh raw materials such as lithium salt (purity ≥ 99.9%), phosphorus-containing compound (analytical grade), manganese salt (purity ≥ 99.9%), ferrous salt (purity ≥ 99.9%) and appropriate amount of complexing agent raw materials according to a certain molar ratio; the molar ratio of lithium salt: phosphorus-containing compound: manganese salt: ferrous salt = 1: (1.1-1.3): x: (1-x), 0.6 < x ≦ 0.8, for example, it can be 1: 1.1: 0.6: 0.4, 1: 1.2: 0.7: 0.3 or 1: 1.3: 0.8: 0.2; but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. In this step, the phosphorus-containing compound needs to be appropriately excessive to increase the conversion rate of the lithium salt; the molar ratio of the lithium salt to the complexing agent is 1: 1-2; the complexing agent can be appropriately excessive;
[0043] The above raw materials are added with water at a liquid-to-solid ratio of 3 to 4:1 to prepare lithium salt solution, manganese salt solution, ferrous salt solution, phosphorus compound solution, and complexing agent solution, respectively, and fully stirred with a mechanical stirrer until all raw materials are completely dissolved and a clear solution is formed, and each solution is preheated to 70° C. to 90° C. in a constant temperature water bath; the temperature after preheating can be, for example, 70° C., 80° C., or 90° C.; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable;
[0044] The above raw materials use lithium salts, phosphorus-containing compounds, manganese salts, ferrous salts and complexing agents permitted in the art. For example, lithium salts include but are not limited to lithium hydroxide monohydrate, lithium nitrate, lithium acetate, lithium chloride or lithium oxalate; manganese salts include but are not limited to manganese acetate, manganese carbonate, manganese sulfate or manganese chloride; the ferrous salts include but are not limited to ferrous nitrate, ferrous sulfate or ferrous chloride; phosphorus-containing compounds include but are not limited to phosphoric acid, diammonium phosphate or triammonium phosphate; complexing agents include but are not limited to citric acid.
[0045] S12, while continuously stirring and keeping warm, firstly mix the manganese salt solution and the complexing agent solution, then sequentially add the ferrous salt solution, the phosphorus compound solution and the lithium salt solution, and dropwise add concentrated ammonia water to obtain a reaction solution with a pH of 2 to 5;
[0046] S13, placing the reaction solution in an ultrasonic-microwave combined reaction system, and sequentially performing ultrasonic treatment alone, ultrasonic-microwave synergistic treatment, and microwave treatment alone to obtain a fluffy honeycomb dry gel;
[0047] The specific operations are as follows:
[0048] (1) placing a reaction container containing a reaction solution in an ultrasonic-microwave combined reaction system, first turning on only the ultrasonic dispersion device, subjecting the reaction solution to ultrasonic treatment, with an ultrasonic power of 200 W to 400 W and a treatment time of 10 min to 30 min, so that the reaction solution is fully mixed and uniform; during the reaction process, a container containing a certain amount of deionized water needs to be placed in the ultrasonic-microwave combined reaction system to prevent the wet gel from causing the system to run idle in the later stage of drying; the ultrasonic power can be 200 W, 300 W, or 400 W, and the treatment time can be 10 min, 20 min, or 30 min; but it is not limited to the values listed, and other values not listed within the numerical range are also applicable;
[0049] (2) On the basis of continuous ultrasonic treatment, a microwave heating device is turned on to perform ultrasonic-microwave synergistic treatment, the microwave power is set to 250W-500W, and the reaction time is 30min-60min; the microwave power can be 250W, 350W, 500W, and the ultrasonic-microwave synergistic treatment time can be 30min, 45min, 60min; but it is not limited to the listed values, and other values not listed in the numerical range are also applicable;
[0050] (3) When the reaction solution turns into a yellow sol, the ultrasonic dispersion device is turned off and the microwave heating treatment is continued until a fluffy honeycomb dry gel is formed.
[0051] The steps of the present invention utilize the fast and uniform heating characteristics of microwaves, so that the reaction system reaches a uniform temperature distribution in a short time, thereby effectively and accurately controlling the temperature of the gelation process, shortening the gelation and time, replacing the long-term hydrothermal evaporation and aging steps in the sol-gelation process, and improving production efficiency; at the same time, assisted by ultrasonic dispersion technology, making full use of its cavitation effect and mechanical vibration, the strong crushing effect of ultrasound can break the agglomerates in the gel, so that the particles are evenly dispersed, ensuring that the solute is fully mixed, and achieving uniform dispersion of the substance in the gel state, further promoting the reaction. This helps to reduce the interaction force between particles in the sol-gelation process, prevent the occurrence of agglomeration, and thus prepare a more uniform particle size distribution, a more compact and orderly microstructure, and greatly improve the electronic conductivity and stability of the material.
[0052] S14, thermally decomposing the dry gel, mixing the obtained product with the carbon source according to a preset ratio, and then grinding and demagnetizing the mixture in sequence to obtain a precursor powder;
[0053] The specific operations are as follows:
[0054] (1) placing the dry gel in a muffle furnace, heating to 300° C. to 400° C. for thermal decomposition treatment for 3 h to 6 h; the thermal decomposition temperature may be 300° C., 350° C., or 400° C., and the treatment time may be 3 h, 4.5 h, or 6 h, but is not limited to the values listed, and other values not listed within the numerical range are also applicable;
[0055] (2) After cooling to room temperature in the furnace, the pyrolysis product is taken out, and the pyrolysis product is mixed with a carbon source (preferably glucose or sucrose) in a mass ratio of 8 to 12:1 and ground to obtain a uniform mixed powder; the mass ratio can be 8:1, 10:1, 12:1, but is not limited to the listed values, and other values not listed in the numerical range are also applicable;
[0056] (3) The mixed powder is placed in a rotating demagnetizer and subjected to a demagnetization treatment in a magnetic field of 4000GS to 6000GS for 8 to 12 minutes to obtain a precursor powder. The magnetic field strength may be 4000GS, 5000GS, or 6000GS, and the treatment time may be 8 minutes, 10 minutes, or 12 minutes, but is not limited to the values listed, and other values not listed within the numerical range are also applicable.
[0057] S15. In a microwave reaction system, the precursor powder is subjected to 200W to 450W microwave gradient high temperature sintering under protective atmosphere conditions, and the powder product LiMn is obtained after cooling. x Fe 1-x PO4 / C is a lithium manganese iron phosphate composite positive electrode material.
[0058] The specific operations are as follows:
[0059] (1) First, sintering for 15 minutes at a microwave power of 200W to 250W; the microwave power can be 200W, 230W, or 250W, but is not limited to the values listed, and other values not listed within the numerical range are also applicable; in this stage, the sintering temperature is controlled between 300°C and 450°C;
[0060] (2) Then sintering at a microwave power of 350W to 450W for 20min to 30min; the microwave power can be 350W, 400W, 450W, and the sintering time can be 20min, 25min, 30min; but it is not limited to the values listed, and other values not listed in the numerical range are also applicable; in this stage, the sintering temperature is controlled between 800℃ and 1000℃;
[0061] (3) Finally, the final powder product LiMn is obtained after cooling in the furnace x Fe 1-x PO4 / C;
[0062] During the high temperature sintering process, the pressure is controlled to be 0.01MPa to 0.5MPa; a flowing inert atmosphere (such as argon, nitrogen or helium) is also required to be used for protection to prevent oxidation of the product. The pressure can be 0.1MPa, 0.25MPa, 0.5MPa, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0063] The sintering of the present invention adopts microwave gradient high temperature sintering. Microwave heating can directly act on the molecules of the material, so that the reaction system can reach a uniform temperature distribution in a short time, thereby effectively and accurately controlling the temperature during sintering, shortening the sintering time, and improving production efficiency; in addition, in the initial stage of microwave sintering, a lower microwave power is used to gradually heat the material to avoid the structural damage of the material caused by the rapid temperature change. Subsequently, the microwave power is increased in a gradient, which can more effectively promote the reaction degree of the material, shorten the time required for the overall sintering reaction, and maintain the structure and performance of the material.
[0064] Example 1
[0065] A method for preparing a lithium manganese iron phosphate composite positive electrode material based on a sol-gel method, the method comprising the following steps:
[0066] S11. Weigh lithium hydroxide monohydrate (41.96 g, 1.0 eq, purity ≥ 99.9%), ammonium dihydrogen phosphate (126.53 g, 1.1 eq, analytical grade), manganese acetate (103.81 g, 0.6 eq, purity ≥ 99.9%), ferrous chloride (50.7 g, 0.4 eq, purity ≥ 99.9%), and citric acid (384.28 g, 2 eq); add deionized water at a liquid-to-solid ratio of 3:1 to dissolve in a beaker; stir mechanically in a water bath at 70° C. until the solution is clear;
[0067] S12, under continuous stirring and keeping warm at 70° C., the manganese acetate solution and the citric acid solution were preferentially mixed and mechanically stirred at a speed of 300 r / min for 20 min, and then the ferrous chloride solution, the ammonium dihydrogen phosphate solution and the lithium hydroxide solution were poured in sequence, and finally concentrated ammonia was slowly added dropwise to adjust the pH value of the solution to 5 to obtain a reaction solution;
[0068] S13, transferring the reaction solution to a beaker, and then placing it in an ultrasonic microwave combined reaction system, and placing a beaker containing a certain amount of deionized water; first, only turning on the ultrasonic dispersion device, and performing ultrasonic treatment for 10 minutes at an ultrasonic power of 200 W, so that the reaction solution is fully mixed; on the basis of continuous ultrasonic treatment, turning on the microwave heating device, and performing ultrasonic-microwave synergistic treatment for 60 minutes at a microwave power of 250 W, when the reaction solution is converted into a yellow sol, turning off the ultrasonic dispersion device and continuing the microwave heating treatment until a fluffy honeycomb dry gel is formed;
[0069] S14, placing the honeycomb dry gel in a muffle furnace, thermally decomposing it at 300°C for 6 hours, taking out the product after cooling it to room temperature, mixing the thermal decomposition product with glucose in a mass ratio of 8:1, putting it into an agate mortar for mixed grinding, placing the mixed powder in a rotary demagnetizer, demagnetizing it in a magnetic field of 5000GS for 10 minutes, and obtaining a precursor powder;
[0070] S15, placing the precursor powder in a microwave reaction system, controlling the pressure to 0.1 MPa, first sintering at a microwave power of 200 W and a temperature of 300°C to 450°C for 15 min, then sintering at a microwave power of 350 W and a temperature of 800°C to 1000°C for 30 min; maintaining an argon atmosphere during the sintering process; then cooling in the furnace to obtain the final powder product LiMn 0.6 Fe 0.4 PO4 / C.
[0071] The LiMn prepared in this example 0.6 Fe 0.4 The charge and discharge specific capacity of PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0072] Example 2
[0073] A method for preparing a lithium manganese iron phosphate composite positive electrode material based on a sol-gel method, the method comprising the following steps:
[0074] S11, weigh lithium nitrate (68.95 g, 1.0 eq, purity ≥ 99.9%), phosphoric acid (127.4 g, 1.3 eq, analytical grade), manganese nitrate (143.16 g, 0.8 eq, purity ≥ 99.9%), ferrous nitrate (35.97 g, 0.2 eq, purity ≥ 99.9%), and citric acid (384.28 g, 2 eq); add deionized water at a liquid-to-solid ratio of 4:1 to dissolve in a beaker; stir mechanically in a water bath at 90°C until the solution is clear;
[0075] S12, under continuous stirring and heat preservation at 90° C., the manganese acetate solution and the citric acid solution were preferentially mixed and mechanically stirred at a speed of 300 r / min for 20 min, and then the ferrous chloride solution, the diammonium phosphate solution and the lithium hydroxide solution were poured in sequence, and finally concentrated ammonia was slowly added dropwise to adjust the pH of the solution to 2 to obtain a reaction solution;
[0076] S13, transferring the reaction solution to a beaker, and then placing it in an ultrasonic microwave combined reaction system, and placing a beaker containing a certain amount of deionized water; first, only turning on the ultrasonic dispersion device, and performing ultrasonic treatment for 30 minutes at an ultrasonic power of 400 W, so that the reaction solution is fully mixed; on the basis of continuous ultrasonic treatment, turning on the microwave heating device, and performing ultrasonic-microwave synergistic treatment for 30 minutes at a microwave power of 500 W, when the reaction solution is converted into a yellow sol, turning off the ultrasonic dispersion device and continuing the microwave heating treatment until a fluffy honeycomb dry gel is formed;
[0077] S14, placing the honeycomb dry gel in a muffle furnace, thermally decomposing it at 400°C for 3 hours, taking out the product after cooling it to room temperature, mixing the thermal decomposition product with glucose at a mass ratio of 12:1, putting it into an agate mortar for mixed grinding, placing the mixed powder in a rotary demagnetizer, demagnetizing it in a magnetic field of 5000GS for 10 minutes, and obtaining a precursor powder;
[0078] S15, placing the precursor powder in a microwave reaction system, controlling the pressure to be 0.5 MPa, first sintering at a microwave power of 250 W and a temperature of 300°C to 450°C for 15 min, and then sintering at a microwave power of 450 W and a temperature of 800°C to 1000°C for 20 min; maintaining an argon atmosphere during the sintering process; and then cooling in the furnace to obtain the final powder product LiMn 0.8 Fe 02 PO4 / C.
[0079] The LiMn prepared in this example 0.8 The charge and discharge specific capacity of Fe02PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0080] Example 3
[0081] A method for preparing a lithium manganese iron phosphate composite positive electrode material based on a sol-gel method, the method comprising the following steps:
[0082] S11, weigh lithium chloride (42.39 g, 1.0 eq, purity ≥ 99.9%), triammonium phosphate (178.87 g, 1.2 eq, analytical grade), manganese chloride (113.31 g, 0.7 eq, purity ≥ 99.9%), ferrous sulfate (45.57 g, 0.3 eq, purity ≥ 99.9%), and citric acid (384.28 g, 2 eq); add deionized water at a liquid-to-solid ratio of 4:1 to dissolve in a beaker; stir mechanically in a water bath at 80°C until the solution is clear;
[0083] S12, under continuous stirring and heat preservation at 80° C., the manganese acetate solution and the citric acid solution were preferentially mixed and mechanically stirred at a speed of 300 r / min for 20 min, and then the ferrous chloride solution, the diammonium phosphate solution and the lithium hydroxide solution were poured in sequence, and finally concentrated ammonia was slowly added dropwise to adjust the pH value of the solution to 4 to obtain a reaction solution;
[0084] S13, transferring the reaction solution to a beaker, and then placing it in an ultrasonic microwave combined reaction system, and placing a beaker containing a certain amount of deionized water; first, only turning on the ultrasonic dispersion device, and performing ultrasonic treatment for 20 minutes at an ultrasonic power of 300 W, so that the reaction solution is fully mixed; on the basis of continuous ultrasonic treatment, turning on the microwave heating device, and performing ultrasonic-microwave synergistic treatment for 50 minutes at a microwave power of 350 W, when the reaction solution is converted into a yellow sol, turning off the ultrasonic dispersion device and continuing the microwave heating treatment until a fluffy honeycomb dry gel is formed;
[0085] S14, placing the honeycomb dry gel in a muffle furnace, thermally decomposing it at 350°C for 5 hours, taking out the product after cooling it to room temperature, mixing the thermal decomposition product with sucrose at a mass ratio of 10:1, putting it into an agate mortar for mixed grinding, placing the mixed powder in a rotary demagnetizer, demagnetizing it in a magnetic field of 6000GS for 8 minutes, and obtaining a precursor powder;
[0086] S15, placing the precursor powder in a microwave reaction system, controlling the pressure to be 0.25 MPa, first sintering at a microwave power of 230 W and a temperature of 300°C to 450°C for 15 min, then sintering at a microwave power of 400 W and a temperature of 800°C to 1000°C for 25 min; maintaining a nitrogen atmosphere during the sintering process; then cooling in the furnace to obtain the final powder product LiMn 0.7 Fe 0.3 PO4 / C.
[0087] The LiMn prepared in this example 0.7 Fe 0.3 The charge and discharge specific capacity of PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0088] Comparative Example 1
[0089] Comparative Example 1 is a method for preparing lithium manganese iron phosphate composite positive electrode material based on the sol-gel method. The difference between this method and Example 1 is only in step S13, which uses ultrasonic treatment alone throughout the whole process. The other steps and reaction conditions are the same as those in Example 1.
[0090] Step S13 of this comparative example 1 is specifically as follows: placing the reaction solution in an ultrasonic reaction system, and performing ultrasonic treatment at an ultrasonic power of 200 W until a dry gel is formed.
[0091] The LiMn prepared in Comparative Example 1 0.6 Fe 0.4 The charge and discharge specific capacity of PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0092] Comparative Example 2
[0093] Comparative Example 2 is a method for preparing lithium manganese iron phosphate composite positive electrode material based on the sol-gel method. The difference between this method and Example 1 is only in step S13, which uses microwave treatment alone throughout the whole process. The other steps and reaction conditions are the same as those in Example 1.
[0094] Step S13 of this comparative example 2 is specifically as follows: placing the reaction solution in a microwave reaction system, placing a beaker filled with a certain amount of deionized water, and performing microwave treatment at a microwave power of 250 W until a dry gel is formed.
[0095] The LiMn prepared in Comparative Example 2 0.6 Fe 0.4 The charge and discharge specific capacity of PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0096] Comparative Example 3
[0097] Comparative Example 3 is a method for preparing lithium manganese iron phosphate composite positive electrode material based on the sol-gel method. The difference between this method and Example 1 is only in step S13, which uses ultrasonic and microwave synergistic treatment throughout the process. The other steps and reaction conditions are the same as those in Example 1.
[0098] Step S13 of this comparative example 3 is specifically as follows: transferring the reaction solution into a beaker, and then placing it in an ultrasonic-microwave combined reaction system, while placing a beaker containing a certain amount of deionized water; performing ultrasonic-microwave synergistic treatment under the conditions of a microwave power of 250 W and an ultrasonic power of 200 W until a dry gel is formed.
[0099] The LiMn prepared in Comparative Example 3 0.6 Fe 0.4 The charge and discharge specific capacity of PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0100] Comparative Example 4
[0101] Comparative Example 4 is a method for preparing lithium manganese iron phosphate composite positive electrode material based on the sol-gel method. The difference between this method and Example 1 is only in step S15, in which constant microwave low power is used for sintering treatment throughout the process, and the other steps and reaction conditions are the same as those in Example 1.
[0102] Step S15 of this comparative example 4 is as follows: placing the precursor powder in a microwave reaction system, controlling the pressure to 0.1 MPa, sintering for 60 min at a microwave power of 200 W, and maintaining an argon atmosphere during the sintering process; then cooling the system in the furnace to obtain the final powder product LiMn 0.6 Fe 0.4 PO4 / C.
[0103] The LiMn prepared in Comparative Example 4 0.6 Fe 0.4 The charge and discharge specific capacity of PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0104] Comparative Example 5
[0105] This comparative example 5 is a method for preparing lithium manganese iron phosphate composite positive electrode material based on the sol-gel method. The difference between this method and Example 1 is only in step S15, which uses constant microwave high power for sintering treatment throughout the process. The other steps and reaction conditions are the same as those in Example 1.
[0106] The specific step S15 of this comparative example 5 is as follows: placing the precursor powder in a microwave reaction system, controlling the pressure to 0.1 MPa, sintering at a microwave power of 350 W for 40 min, and maintaining an argon atmosphere during the sintering process; then cooling the system in the furnace to obtain the final powder product LiMn 0.6 Fe 0.4 PO4 / C.
[0107] The LiMn prepared in Comparative Example 5 0.6 Fe 0.4 The charge and discharge specific capacity of PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0108] Comparative Example 6
[0109] Comparative Example 6 is a method for preparing lithium manganese iron phosphate composite positive electrode material based on the sol-gel method. The difference between this method and Example 1 is only in step S15, which adopts conventional high-temperature sintering. The other steps and reaction conditions are the same as those in Example 1.
[0110] Step S15 of this comparative example 6 is as follows: the precursor powder is sintered at 600°C for 10 hours under an argon atmosphere and a pressure of 0.1 MPa; and then cooled in the furnace to obtain the final powder product LiMn 0.6 Fe 0.4 PO4 / C.
[0111] The LiMn prepared in Comparative Example 6 0.6 Fe 0.4 The charge and discharge specific capacity of PO4 / C material was tested at discharge rates of 1C and 2C, and the results are shown in Table 1.
[0112] In order to conduct the charge and discharge specific capacity test, it is usually necessary to make the prepared lithium manganese iron phosphate composite positive electrode material into an electrode plate, and then assemble it into a battery; specifically, the lithium manganese iron phosphate composite positive electrode material, the binder PVDF and the conductive agent acetylene black are mixed in a high-energy ball mill at a mass ratio of 8:1:1 to obtain a uniformly mixed black slurry, and then the black slurry is evenly coated on the current collector aluminum foil by a coating machine, and finally dried at 100°C in a vacuum drying oven for 12 hours to obtain a plate; after flattening, it is cut into a circular plate with a diameter of 15 mm; the circular plate is used as the positive electrode, the metal lithium sheet is used as the negative electrode, Celgard 2400 is used as the diaphragm, and 1M LiPF6 EC:DMC (1:1 Vol%) is used as the electrolyte, and a button battery is assembled according to the positive electrode shell → positive electrode plate → diaphragm → lithium sheet → gasket, spring sheet → negative electrode shell, and electrochemical tests such as charge and discharge specific capacity are carried out on a Land electrochemical instrument.
[0113] The button cells made of lithium manganese iron phosphate composite positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were tested for charge and discharge specific capacity at discharge rates of 1C and 2C. The initial discharge capacity and capacity retention rate results obtained after 100 cycles are shown in Table 1.
[0114] Table 1
[0115]
[0116] It can be seen from the data in Table 1 that the lithium manganese iron phosphate composite positive electrode materials prepared in Examples 1 to 3 of the present invention have good discharge specific capacity and capacity retention rate, and exhibit excellent dispersion uniformity, electronic conductivity and stability.
[0117] Comparison of Comparative Examples 1 to 3 with Example 1 shows that the discharge specific capacity and capacity retention rate of the lithium manganese iron phosphate composite positive electrode material prepared by using single microwave, ultrasonic, and microwave-ultrasonic synergistic treatment in the sol-gel preparation process are lower than those of the ultrasonic, ultrasonic-microwave synergistic, and microwave sequential segmented treatment of the present invention. In terms of effect, single microwave-ultrasonic synergistic treatment> single ultrasonic treatment ≈ single microwave treatment.
[0118] Comparison of Comparative Examples 4 to 5 with Example 1 shows that the discharge specific capacity and capacity retention rate of the lithium manganese iron phosphate composite positive electrode material prepared by step-by-step microwave sintering are better than those by single-power microwave sintering. The reason is that directly using high-power microwaves for sintering will cause rapid temperature changes, thereby causing damage to the material structure; directly using low-power microwaves for sintering will result in low reaction efficiency.
[0119] Comparing Comparative Example 6 with Example 1, it can be seen that the electrochemical performance of the lithium manganese iron phosphate composite positive electrode material prepared by microwave sintering is better than that by conventional sintering, and the time consumption is greatly shortened.
[0120] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium manganese iron phosphate composite positive electrode material based on a sol-gel method, characterized in that: The method comprises the following steps: Preheating the lithium salt solution, the manganese salt solution, the ferrous salt solution, the phosphorus-containing compound solution, and the complexing agent solution to preset temperatures respectively; the phosphorus-containing compound is selected from phosphate or phosphoric acid; Under continuous stirring and heat preservation, the manganese salt solution and the complexing agent solution are first mixed uniformly, and then the ferrous salt solution, the phosphorus compound solution and the lithium salt solution are added in sequence, and concentrated ammonia water is added dropwise to obtain a reaction solution with a pH of 2 to 5; The reaction solution is placed in an ultrasonic-microwave combined reaction system, and is subjected to ultrasonic treatment alone, ultrasonic-microwave synergistic treatment, and microwave treatment alone in sequence to obtain a fluffy honeycomb dry gel; The dry gel is subjected to thermal decomposition treatment, and the obtained product is mixed with a carbon source in a preset ratio, and then ground and demagnetized in sequence to obtain a precursor powder; In the microwave reaction system, the precursor powder was subjected to microwave gradient sintering at 200W to 450W under protective atmosphere conditions, and the powder product LiMn was obtained after cooling. x Fe 1-x PO4 / C is a lithium manganese iron phosphate composite positive electrode material.
2. The method for preparing lithium iron manganese phosphate composite positive electrode material based on the sol-gel method according to claim 1, characterized in that: The reaction solution is placed in an ultrasonic-microwave combined reaction system, and ultrasonic treatment alone, ultrasonic-microwave synergistic treatment, and microwave treatment alone are successively performed to obtain a fluffy honeycomb dry gel. The specific operation is as follows: The reaction container containing the reaction solution is placed in the ultrasonic microwave combined reaction system, and only the ultrasonic dispersion device is turned on to perform ultrasonic treatment on the reaction solution, with the ultrasonic power being 200W to 400W and the treatment time being 10min to 30min; Then, the microwave heating device is turned on for ultrasonic-microwave coordinated treatment, the microwave power is set to 250W-500W, and the reaction time is 30min-60min; When the reaction solution turns into a yellow sol, the ultrasonic dispersion device is turned off and the microwave heating treatment is continued until a fluffy honeycomb dry gel is formed.
3. The method for preparing lithium manganese iron phosphate composite positive electrode material based on the sol-gel method according to claim 2, characterized in that: The ultrasonic-microwave combined reaction system is also provided with a container containing deionized water.
4. The method for preparing lithium iron manganese phosphate composite positive electrode material based on the sol-gel method according to claim 1, characterized in that: The dry gel is thermally decomposed, the obtained product is mixed with a carbon source according to a preset ratio, and then ground and demagnetized in sequence to obtain a precursor powder. The specific operation is as follows: The dry gel is placed in a muffle furnace and heated to 300°C to 400°C for thermal decomposition for 3h to 6h; After cooling to room temperature in the furnace, the pyrolysis product is taken out, and the pyrolysis product is mixed with the carbon source in a mass ratio of 8 to 12:1 and ground to obtain a uniform mixed powder; The mixed powder is placed in a rotating demagnetizer and subjected to a demagnetization treatment in a magnetic field of 4000GS to 6000GS for 8 minutes to 12 minutes to obtain a precursor powder.
5. The method for preparing lithium iron manganese phosphate composite positive electrode material based on the sol-gel method according to claim 4, characterized in that: The carbon source is selected from glucose or sucrose.
6. The method for preparing lithium iron manganese phosphate composite positive electrode material based on the sol-gel method according to claim 1, characterized in that: In the microwave reaction system, the precursor powder is subjected to microwave gradient sintering at 200W to 450W under protective atmosphere conditions. The specific operation is as follows: First, sinter at a microwave power of 200W to 250W for 15min; Sintering at a microwave power of 350W to 450W for 20min to 30min; After cooling in the furnace, the final powder product LiMn x Fe 1-x PO4 / C; Among them, the pressure during the sintering process is controlled to be 0.01MPa~0.5MPa.
7. The method for preparing lithium iron manganese phosphate composite positive electrode material based on the sol-gel method according to claim 6, characterized in that: The sintering temperature is 300°C to 450°C at a microwave power of 200W to 250W; the sintering temperature is 800°C to 1000°C at a microwave power of 350W to 450W.
8. The method for preparing lithium iron manganese phosphate composite positive electrode material based on the sol-gel method according to claim 1, characterized in that: The lithium salt is selected from lithium hydroxide monohydrate, lithium nitrate, lithium acetate, lithium chloride or lithium oxalate; The manganese salt is selected from manganese acetate, manganese carbonate, manganese sulfate, manganese nitrate or manganese chloride; The ferrous salt is selected from ferrous nitrate, ferrous sulfate or ferrous chloride; The phosphate is selected from diammonium phosphate or triammonium phosphate; According to the molar ratio, lithium salt: phosphorus-containing compound: manganese salt: ferrous salt = 1: (1.1-1.3): x: (1-x), 0.6≦x≦0.
8.
9. The method for preparing lithium iron manganese phosphate composite positive electrode material based on the sol-gel method according to claim 8, characterized in that: The complexing agent is selected from citric acid; the molar ratio of lithium salt to complexing agent is 1:1-2.
10. The method for preparing lithium iron manganese phosphate composite positive electrode material based on the sol-gel method according to claim 1, characterized in that: The preset temperature for preheating is 70℃~90℃.
Citation Information
Patent Citations
Method for preparing nanometer-level lithium iron phosphate by ultrasonic wave-microwave alternating method
CN102115068A
Novel method for preparing lithium iron phosphate positive electrode material based on colloid framework
CN106207173A
Cited By
Preparation method of rare earth modified antibacterial polymer master batch
CN121851423A